Step by Step: Kinematics of the Reciprocal Trail Making Task Predict Slowness of Activities of Daily Living Performance in Alzheimer’s Disease - Gulde, Philipp; Leippold, Katharina; Kohl, Sarah; Grimmer, Timo; Diehl-Schmid, Janine; Armstrong, Alan; Hermsdörfer, Joachim (Frontiers in Neurology, 2018)
Dementia impairs the ability to perform everyday activities. Reduced motor capacity and executive functions as well as loss of memory function and forms of apraxia and action disorganization syndrome can be reasons for such impairments. In this study, an analysis of the hand trajectories during the sequential movements in an adapted version of the trail making task, the reciprocal trail making task, was used to predict performance in activities of daily living of patients suffering from mild cognitive impairment and dementia. 1 patients with dementia of the Alzheimer’s type and 15 healthy, age-matched adults were tested in the standardized activities of daily living of tea making and document filing. The characteristics of the kinematic performance in the reciprocal trail making task was assessed and models of multiple linear regression were computed in order to predict the durations of the activities of daily living. Patients showed increased trial durations in the ADL (Cohen’s d: tea making 1.64, document filing 1.25). Parameters and explained variability differed across patients and control as well as between different activities. The models for the patient sample were stronger and particularly high for the document filing task for which kinematics explained 71% of the variance (R_adjusted^2: tea making 0.62, document filing 0.71; both tasks combined patients 0.55, controls 0.25). The most relevant factors for the models were the trial duration and a parameter characterizing movement fluency and variability (“movement harmonicity”) in the reciprocal trail making task. The models of multiple linear regression suggested that the patients’ activity of daily living performance was limited by cognitive demands, namely identifying the varying targets during sequencing, and the healthy controls’ performance by their motor capacity. Such models could be used to estimate the severity of ADL impairments in patients.